HUBUNGAN PENGETAHUAN IBU HAMIL PRIMIGRAVIDA TRIMESTER III TENTANG PRE-EKLAMSIA DENGAN UPAYA PENCEGAHAN TERJADINYA EKLAMSIA - Mubaidah, Siti; Lestari, Ani; Lestari, Ani (Jurnal AKP, 2011)
In Indonesia, pre-eclampsia are main causes of mortality for mother and fetus. The purpose of this study is to know the correlation between knowledge of pregnant woman primigravida trimester III about pre-eclamsia with the efforts to prevent the incidence of eclamsia in Gynecology Clinic of Pare Public Hospital Kediri.The research design used in this study was a non experimental with cross sectional approach. The population was all pregnant women primigravida trimester III who attended to Gynecology clinic of Pare Public Hospital in May 2010. Sample size was 15 respondents. The research instruments were questionnaire, which the data was analyzed by using Spearman correlations.Results were obtained with 7 respondents (46.7%) have sufficient knowledge and 8 respondents (53.3%) had adequate prevention efforts, based on Spearman analysis was obtained significance value (r) 0.009 with an error rate (Î±) 0.05. Thus r < Î± means that H1 is received it means there is a correlation between knowledge of pregnant women primigravida trimester III about pre-eclampsia with efforts to prevent the occurrence of eclampsia, while H0 is rejected. Where as for respondents who have less knowledge but good prevention efforts or simply because they were housewives who had plenty of time at home to access information relating to the prevention efforts of health workers, thus can be concluded that for the prevention of eclampsia is better required good knowledge of pre-eclampsia